New biological potential of abietane diterpenoids isolated from Salvia austriaca against microbial virulence factors. (September 2016) - Sadowska, Beata; Kuźma, Łukasz; Micota, Bartłomiej; Budzyńska, Aleksandra; Wysokińska, Halina; Kłys, Arkadiusz; Więckowska-Szakiel, Marzena; Różalska, Barbara
Abstract: The increasing importance of multi-resistant strains and microbial biofilms in the development of chronic infections has driven the search for more effective alternative therapy including plant-origin preparations. The present study evaluates the broadly-defined antimicrobial activity of two abietane diterpenoids isolated from Salvia austriaca transformed roots: taxodone and 15-deoxy-fuerstione. The direct biostatic/biocidal effect of these phytocompounds and their influence on Staphylococcus aureus and Candida albicans virulence factors/mechanisms (adhesion, biofilm formation, agglutination in human plasma, survival in the blood, germ tube and mycelium formation) were tested using in vitro assays. Both phytocompounds significantly inhibited microbial adhesion and biofilm formation when used at ½ and ¼ MIC. Additionally, taxodone was able to limit staphylococcal survival in human blood, as well as C. albicans germ tube formation and hyphal growth. The tested diterpenoids express significant anti-biofilm activity against both staphylococci and yeast, and adversely affect their virulence factors/mechanisms, which are relevant in the course of the infection in vivo . Therefore, they demonstrate considerable biomedical potential as complements for classic therapy with antibiotics. Graphical abstract: